Friday on my mind: Working time in the manufacturing sector - Torsten Müller (European Trade Union Institute (ETUI), 2023)
The twin digital and green transition will have far-reaching labour market consequences in the manufacturing sector as regards the quantity, character and quality of employment. The effects of transition will be uneven between countries and regions, different industries and different categories of workers, depending on their various socio-economic starting points and the different degrees to which they are affected by the twin transition. Against this background, industriAll is calling for a just transition that is fair for all workers and that does not destroy, but rather preserves quality employment. Working time policy more generally and working time reduction more specifically is an important tool for achieving such a just transition by helping to safeguard employment and ensure good working and living conditions.
Keywords: 330; Arbeitszeit; Arbeitszeitgestaltung; Industrie; Strukturwandel; EU-Staaten